Polychemotherapy with Curcumin and Doxorubicin via Biological Nanoplatforms: Enhancing Antitumor Activity - Milad Ashrafizadeh; Ali Zarrabi; Farid Hashemi; Amirhossein Zabolian; Hossein Saleki; Morteza Bagherian; Negar Azami; Atefe Kazemzade Bejandi; Kiavash Hushmandi; Hui Li Ang; Pooyan Makvandi; Haroon Khan; et al. (MDPI AG, 2020)
Doxorubicin (DOX) is a well-known chemotherapeutic agent extensively applied in the field of cancer therapy. However, similar to other chemotherapeutic agents such as cisplatin, paclitaxel, docetaxel, etoposide and oxaliplatin, cancer cells are able to obtain chemoresistance that limits DOX efficacy. In respect to dose-dependent side effect of DOX, enhancing its dosage is not recommended for effective cancer chemotherapy. Therefore, different strategies have been considered for reversing DOX resistance and diminishing its side effects. Phytochemical are potential candidates in this case due to their great pharmacological activities. Curcumin is a potential antitumor phytochemical isolated from Curcuma longa with capacity of suppressing cancer metastasis and proliferation and affecting molecular pathways. Experiments have demonstrated the potential of curcumin for inhibiting chemoresistance by downregulating oncogene pathways such as MMP-2, TGF-β, EMT, PI3K/Akt, NF-κB and AP-1. Furthermore, coadministration of curcumin and DOX potentiates apoptosis induction in cancer cells. In light of this, nanoplatforms have been employed for codelivery of curcumin and DOX. This results in promoting the bioavailability and internalization of the aforementioned active compounds in cancer cells and, consequently, enhancing their antitumor activity. Noteworthy, curcumin has been applied for reducing adverse effects of DOX on normal cells and tissues via reducing inflammation, oxidative stress and apoptosis. The current review highlights the anticancer mechanism, side effects and codelivery of curcumin and DOX via nanovehicles.